Pengaruh Gugus Fungsi Karbon Aktif Tatal Karet terhadap Parameter Air Limbah Karet - Tri Sucy Angrainy; Siti Umi Kalsum; Marhadi Marhadi (Universitas Batanghari Jambi, 2026)
Rubber manufacturing operations inevitably yield effluent and solid residues bearing environmentally detrimental characteristics if left inadequately managed. Valorization of rubber shaving residues into activated carbon represents a compelling remediation pathway. This investigation scrutinized the influence of functional moieties within rubber shaving-derived activated carbon upon rubber mill effluent parameters through an experimental quantitative-qualitative design. Physicochemical attributes were elucidated via FTIR to delineate surface-bound functional assemblages, whilst remediation efficacy was appraised against BOD, TSS, and pH indices. Spectroscopic interrogation revealed oxygen-enriched moieties encompassing hydroxyl (-OH), carbonyl (-C=O), and ether (-C-O) constituents, each exerting a pivotal role in adsorptive mechanisms. Notwithstanding anomalous BOD elevation in non-activated specimens, NaOH 10% activation demonstrably consolidated functional assemblages, substantially curtailing BOD concentrations. This study affirms that rubber shaving-derived activated carbon constitutes an efficacious and ecologically benign adsorbent, wherein judicious activation optimization emerges as the cardinal determinant of successful pollutant abatement.